Agentes microbianos en el instrumental endodóntico según el protocolo de esterilización en calor seco y húmedo - Quezada Cumbicos, Verónica del Cisne (2019)
In clinical practice, the physical characteristics of the instruments used in endodontics, it is observed that the design of its stretch marks, irregularities and cutting angles facilitates the retention of detritus and microorganisms, thus hindering a complete removal of the biological material during the cleaning, disinfection and sterilization process. This study aims to verify the presence of microorganisms in endodontic instruments. The method used in this research was performed randomly in the facilities of the Dental Clinic No. 1 of the National University of Loja, for which 100 files of different students who completed their endodontic treatments were selected. Then, 50 treatment files were taken in adults ( type K files, 8 endodontic treatments) and 50 treatment files in children (type H files, 7 endodontic treatments) they were subjected to sterilization processes in dry heat and humid heat, to be later taken to the laboratory of the Medilab clinic in the city of Loja. The result obtained indicates that the type K files submitted to the wet heat sterilization process were the most contaminated by aerobic bacteria, where they presented a bacteriological count of 280,000 CFU / ml, while type H files obtained an average of 260,000 CFU / ml. Conclusion: the bacteria found in the type K files submitted to the wet heat sterilization process were Escherichia coli 23.08%, Streptococcus beta-hemolytic group A 26.92%, Streptococcus spp 26.92% and Staphylococcus saprophyticus with 23.08%. Meanwhile, the bacterium found in type H files submitted to the dry heat sterilization process was Staphylococcus aureus Meticilino sensible, Bacillus spp, and Staphylococcus saprophyticus with 33.33% each one. As a recommendation, undergraduate students should continue to be made aware of the importance of proper cleaning and disinfection of the instruments to be used. Keywords: microorganisms, aerobic bacteria, endodontic files, sterilization.